An organic–inorganic hybrid interlayer for improved electron extraction in inverted polymer solar cells. Issue 13 (26th January 2016) - Lee, Eui Jin; Heo, Soo Won; Han, Yong Woon; Moon, Doo Kyung
Abstract : The electron extraction of inverted polymer solar cells (PSCs) was enhanced by modifying surface energy of buffer layer. We introduced organic–inorganic hybrid ZnO–PFN interlayer as electron extraction layer. Abstract : We fabricated inverted polymer solar cells (PSCs) using an organic–inorganic hybrid interlayer for electron extraction. The surface energy and surface defects of an organic–inorganic ZnO–PFN hybrid film, which was prepared by dissolving the conjugated polymer electrolyte poly[(9, 9-bis(3′-( N, N -dimethylamino)propyl)-2, 7-fluorene)- alt -2, 7-(9, 9-dioctyl-fluorene)] (PFN) in a ZnO solution, were reduced, compared to ZnO film. By introducing the ZnO–PFN electron extraction layer, the interfacial contact between the active and electron extraction layers was improved and the series resistance of the PSC device was decreased. As a result, electron extraction from the active layer to the electrode was enhanced. The highest power conversion efficiency (PCE) of the inverted PSCs was 9.2%. Moreover, the ZnO–PFN-based inverted PSCs showed improved long-term stability compared to ZnO-based devices. The ZnO–PFN interlayer aimed to overcome the drawbacks of the conventional hydrophilic surface of ZnO, based on the properties of the conjugated polymer (PFN) without the need for additional processes. It was therefore simple to fabricate the inverted PSCs, making the devices commercially viable.